Karawang Spot Billiard Employee Training - Dicky Wahyu Effendi; Nanda Agung Hernawan; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Formosa Journal of Applied Sciences, 2023)
Spot Billiard Karawang is a billiard service business that also sells billiard equipment with targeted marketing to teenagers who like the sport of billiards. To meet marketing targets, Spot Billiard must have an appropriate strategy. Employee training is one of the methods used by Spot Billiards to control the quality of service produced to meet targets and customer satisfaction. This made the author interested in researching Spot Billiards by discussing how employee training improves the quality of company services. This visit method is a field visit (field research) located at Spot Billiards jl. Tuparev no 16, Karawang Electronic Center lt 2, Karawang City. The primary data was obtained through interviews, observation and documentation.